(untitled) (Journal of Advanced Research in Social Sciences, 2023)
In 2018, Every Mind responded to a lack of research into supports for carers of a person with depressive or anxiety symptoms, by designing, piloting, and implementing an online support program targeting these carers. Previous publications have documented several benefits of this research, such as the program’s feasibility, acceptability, and trends in efficacy. Although these results are promising, a deeper examination of the societal and economic significance of the research is warranted. The present study utilised the Framework to Assess the Impact from Translational Health Research (FAIT) and examined program documentation to retrospectively assess the benefits, costs and lessons learned from the Minds Together research. The results revealed that the benefits were widespread, particularly in capacity building. The economic analysis found a return on investment of over 80,000 AUD 2022. The study also emphasised the role of research centre staff in communicating and disseminating research findings. The retrospective application of FAIT to the Minds Together program proved feasible and has provided valuable insights. The present study highlights the comprehensive benefits of Minds Together beyond the trial outcomes reported in previous studies and emphasises the advantages of using health economics methodologies to examine the impacts of research targeting informal carers.